2019
DOI: 10.1097/opx.0000000000001365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wavefront-guided and Best Conventional Scleral Lenses after Habituation in Eyes with Corneal Ectasia

Abstract: Significance.-Visual performance with wavefront-guided (WFG) contact lenses has only been reported immediately after manufacture without time for habituation, and comparison has only been made with clinically unrefined predicate conventional lenses. We present comparisons of habitual corrections, best conventional scleral lenses, and WFG scleral lenses after habituation to all corrections. Purpose.-To compare, in a cross-over design, optical and visual performance of eyes with corneal ectasias wearing dispense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 55 publications
1
73
0
Order By: Relevance
“…Other outcomes included the numbers of lenses lost or broken and dropouts during the period surveyed. True logMAR visual acuities, contrast sensitivity, and higher-order aberrations, although important measures of visual performance in scleral lenses, 49 52 were not obtained because they are not readily available in the clinical setting.…”
Section: Methodsmentioning
confidence: 99%
“…Other outcomes included the numbers of lenses lost or broken and dropouts during the period surveyed. True logMAR visual acuities, contrast sensitivity, and higher-order aberrations, although important measures of visual performance in scleral lenses, 49 52 were not obtained because they are not readily available in the clinical setting.…”
Section: Methodsmentioning
confidence: 99%
“…Although the authors reported that both sets of lenses were worn on a ‘daily’ basis, for each eight‐week period, specific data on how many hours of lens wear per day were not presented in their paper. Expectedly, Hastings et al found that the mean HORMS error reduced from +0.46 ± 0.24 μm with the conventional lenses, to +0.26 ± 0.08 μm with the customised lenses (p = 0.004). However, although improved, the difference in the mean area under the log contrast sensitivity function did not reach statistical significance between the two lens types (conventional lenses = 13.91 ± 2.20 log units, customised lenses 15.82 ± 2.34 log units [p = 0.09]).…”
Section: Spot‐imaging Issuesmentioning
confidence: 98%
“…Further studies are needed to explore this concept; for example, it is currently unclear if the degree of neural deficit is related to the severity of the patient's disease and/or age, or whether such deficits could be overcome through regular perceptual learning/training . At present, only one study has explored the impact of allowing keratoconic patients to habituate to a wavefront‐guided, customised scleral lens correction for a substantial time period . Using the customisation methodology outlined in their previous investigation, Hastings et al conducted a randomised study, which included a crossover design, allowing comparisons between ‘conventional’ scleral lenses (acting as a control) and ‘customised’ scleral lenses, over two eight‐week (approximate) periods, for eight patients with keratoconus.…”
Section: Spot‐imaging Issuesmentioning
confidence: 99%
See 2 more Smart Citations